Research on the cultivation of students majoring in preschool education - Wang Qian; Mohd Nazri Abdul Rahman; Cui Xinmian (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
With the arrival of the flood of education informatization, all kinds of preschool education institutions at all levels have carried out information education practice, and achieved good results, but there are still many problems. In todays society, the development of preschool children is closely related to the support of modern information technologyAt present, there are still some defects in the evaluation system and training mode of colleges and universities in the training stage of students majoring in universities. Therefore, this study is based on the actual situation of information education ability of students majoring in preschool education in universities, designs a questionnaire, analyzes and summarizes the survey results, and puts forward suggestions for improving information literacy. It tries to build a scientific training standard for the information education ability of students majoring in preschool education, and to provide effective help for improving the information teaching ability of students majoring in preschool education.